Cartilha de orientação: Sobre segurança do paciente em tratamento oncológico - Sá, Rosana dos Santos (Universidade do Vale do Rio dos Sinos, 2019)
Patient safety has been a relevant topic in recent decades, becoming a key component for improving patient safety in health services provided to cancer users. Patient education and self-care are essential for safety in the care environment. This paper focuses on the development of a guidance booklet on patient safety in cancer treatment. This is a qualitative research with emphasis on an integrative literature review for the construction of a patient safety primer in cancer treatment. The guiding question of this research was elaborated: which scientific productions on the promotion of patient safety in the oncology area that support the construction of a guidebook for patients on cancer treatment? It was used four online databases: Lybrary Electronic Scientific Online (Scielo), Nursing Database (BDENF), Latin American and Caribbean Health Sciences Literature (Lilacs) and National Library of Medicine (PUBMED). Data collection was performed in April 2019, with the following descriptors: Patient Safety, Health Education, Educational Technology and Oncology. As inclusion criteria, we used the Portuguese, English and Spanish languages and full texts related to the theme of patient safety in cancer treatment. We found 291 articles and selected 22, and three categories were identified: (I) patient safety; (II) patient needs and (III) health education. The authors point out strategies aimed at health education of patients undergoing cancer treatment, regarding patient safety, individualized treatment, answering questions about the diagnosis and treatment, as well as pain, signs and symptoms of the disease, in addition to listening by trained professionals, aiming at patient comfort and safety during cancer treatment. The product generated in this study consists of a guidebook on patient safety in cancer treatment. The creation of this booklet enables the patient as well as for the multiprofessional team a more effective communication with a view to individualized care of the patient undergoing cancer treatment.
Keywords: Segurança do paciente; Educação em saúde; Tecnologia educacional; Oncologia; Patient safety; Health education; Educational technology; Oncology; ACCNPQ::Ciências da Saúde::Enfermagem